2013
DOI: 10.4103/0301-4738.116063
|View full text |Cite
|
Sign up to set email alerts
|

Ocular allergy and keratoconus

Abstract: Keratoconus is the most common corneal ectatic disorder, the cause of which is largely unknown. Many factors have been implicated, and the ocular allergy is being one of them. The commonly proposed pathogenesis includes the release of inflammatory mediators due to eye rubbing which may alter the corneal collagen and lead to corneal ectasias. The onset of keratoconus is often early in cases associated with allergy and routine corneal topography may detect subtle forms of keratoconus. These cases may require ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 14 publications
0
56
0
3
Order By: Relevance
“…23,24 Eye rubbing has been postulated as a significant risk factor by several authors. 3,5,7,[25][26][27] However, few studies [8][9][10][11][12][13][14][15] have referred to eye rubbing as the cause of keratoconus; therefore, it has recently attracted attention. Mashor et al 9 reported three patients with Tourette syndrome and asymmetrical or unilateral keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Eye rubbing has been postulated as a significant risk factor by several authors. 3,5,7,[25][26][27] However, few studies [8][9][10][11][12][13][14][15] have referred to eye rubbing as the cause of keratoconus; therefore, it has recently attracted attention. Mashor et al 9 reported three patients with Tourette syndrome and asymmetrical or unilateral keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Lucarelli et al reported another case of corneal ectasia associated with massage for dacryocystoceles [4]. Also eye rubbing has been implicated in the pathogenesis of keratoconus [5][6][7]. These facts lead us to suppose that excessive post-trabeculectomy massage may lead to corneal deformation and even breaks in Descemet membrane, causing stromal and epithelial edema.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the most important nonsurgical treatment measure is guidance not to rub the eyes, 4,9 along with treatment of ocular allergy and optimization of ocular surface. 19 Visual restoration should be first attempted with spectacles or contact lenses. Often requiring specially designed corneal or scleral lenses, contact lens fitting constitute the most effective treatment option.…”
Section: Editorialmentioning
confidence: 99%